DETERMINATION OF NATURAL RESERVES OF THE MEDICINAL PLANT PATRINIA INTERMEDIA ROEM ET SCHULT, GROWING IN THE INNER TIEN SHAN (USING THE EXAMPLE OF THE NARYN REGION) (PROCEEDINGS OF THE NATIONAL ACADEMY OF SCIENCES OF THE KYRGYZ REPUBLIC, 2023)
This article presents scientific information about the natural distribution of medicinal plants in Kyrgyzstan and the conditions of their collective growth with other plants of the natural reserve. Due to the increase in arable land in the country and the expansion of human economicactivity, the number of wild medicinal plants is decreasing. It is recommended to require urgentprotection along with the rational use of natural resources of medicinal plants in the republic andthe rational use of the territories where they are distributed. In the course of research, together withthe distribution of plants in natural conditions, it was established that the medicinal plant Patriniaintermedia grows in different habitats, and also showed details of plant communities.
Keywords: associations, cenopopulation, phytocenology, formation, xerophytes, mesophytes, hamophytes, phanerophytes, xerothermy.